2009
DOI: 10.1016/j.vetmic.2008.10.028
|View full text |Cite
|
Sign up to set email alerts
|

A new emerging genotype subgroup within PCV-2b dominates the PMWS epizooty in Switzerland

Abstract: Postweaning multisystemic wasting syndrome (PMWS) is among the most important emerging pig diseases worldwide. Initially, the insidious nature of the disease made it difficult to pinpoint the pathogen. The presence of porcine circovirus type 2 (PCV2) in all PMWS diseased animals led to its acceptance, possibly together with an unknown factor, as the causative agent for PMWS. Also, presence of PCV2 in healthy individuals did not facilitate the understanding of the disease. Phylogenetic classification separates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
69
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 27 publications
(1 reference statement)
2
69
0
2
Order By: Relevance
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15], China [17,21,38], Cuba [29], Denmark [12], Germany [30], Japan [32], Korea [1,2,19,20], Slovakia [37], Spain [10], Sweden [33], Switzerland [39], Thailand [18] and the U.S.A. [6,23]. PCV2b might be more pathogenic than PCV2a [16,32].…”
mentioning
confidence: 99%
“…The PCV2c genotype has only been found in Denmark to date [31]. In recent years, several reports have suggested that PCV2b is the predominant genotype in many countries worldwide, including Brazil [8,11], Canada [14,15], China [17,21,38], Cuba [29], Denmark [12], Germany [30], Japan [32], Korea [1,2,19,20], Slovakia [37], Spain [10], Sweden [33], Switzerland [39], Thailand [18] and the U.S.A. [6,23]. PCV2b might be more pathogenic than PCV2a [16,32].…”
mentioning
confidence: 99%
“…Despite this high sero-prevalence, few cases of PCVDs were reported in Switzerland before 2003 [15]. The sudden onset of an epizootic correlated with a genetic shift from PCV2a group members to a specific PCV2b group member that we named PCV2b-CH [15].…”
Section: Short Communicationmentioning
confidence: 99%
“…Nevertheless, elevated antibody titers that are due to vaccinations of piglets against PCV2 do not last until finisher stage [13]. Although PCVDs were only described in Switzerland in 2001 [14], PCV2 has been present in the Swiss pig population since at least 1979 [15]. In a prevalence study from 2001-2002, only four out of seventytwo (5%) wasting piglets from 26 different farms were diagnosed with PCV2-systemic disease (PCV2-SD) [16].…”
Section: Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the aid of a signature motif, which was a short amino acid motif encoded within the capsid protein, PCV2 was separated into at least 2 major groups, PCV2a and PCV2b. This classification received more attention, as it seemed to define PCV2b to be more virulent (6). However, little is known about the role of PCV2b in semen from PCV2b-infected male mice and the transmission of PCV2b from semen to fetuses via artificial insemination.…”
mentioning
confidence: 99%